Pharmaceutical interventions in pediatric oncology: integrative literature review (Research, Society and Development, 2023)
This integrative literature review aimed to gather and analyze evidence on pharmaceutical interventions (PI) in pediatric oncology and their acceptance by the multidisciplinary team of antineoplastic therapy. The searches were carried out in PubMed, EMBASE and in the Regional Portal of the Virtual Health Library (BVS), in addition, complementary manual searches were carried out in Google Scholar. We included 24 studies without language and publication date restrictions. The most frequent PI were: dose/dosage adjustment, pharmaceutical guidance, need for additional treatment, adjustment of infusion and dilution rate, most appropriate therapeutic alternative, evaluation of treatment effectiveness, drug suspension, medication conciliation and therapy change. The anticancer drugs most involved in PI were etoposide and vincristine and for supportive treatment: ondansetron and sulfamethoxazole+trimethoprim. The acceptability of the PI ranged from 81 to 100%. The results evidence the role of the clinical pharmacist in the prevention, identification and resolution of drug-related problems in pediatric oncology.